Bioprinting of 3D tissues/organs combined with microfluidics. Issue 39 (19th June 2018) - Ma, Jingyun; Wang, Yachen; Liu, Jing
Abstract : Combinations of 3D bioprinting and microfluidics could complement each other to create artificial tissues and organs with complex architectures. Abstract : Accompanied by the increasing demand for organ transplants and personalized medicine, recent years have witnessed great developments in the regeneration of tissues/organs, which has benefited from various manufacturing technologies, especially 3D bioprinting. In 3D bioprinting, according to the morphogenesis, cellular microenvironment, and biological functions of the native tissues/organs, cells and biomaterials are printed by layer-by-layer assembly to form 3D bio-functional units. However, there are still substantial differences between existing 3D printed constructs and actual tissues and organs, especially in microscale structures such as vascular networks. By manipulating controllable fluids carrying biomolecules, cells, organisms, or chemical agents, microfluidic techniques aim to integrate biological or chemical functional units into a chip. With its features of biocompatibility, flexible manipulation, and scale integration on the micro/nanoscale, microfluidics has been a tool that has enabled the generation of micro-tissues/organs with precise configurations. With the inspiration of these two technologies, there have been efforts to fabricate functional living tissues and artificial organs with complex structures via a combination of 3D bioprinting and microfluidics, which may lead to unexpected effects. In this review, we discuss advances in microfluidics-assisted bioprinting in the engineering of tissues/organs and provide future perspectives for this combination in the generation of highly biomimetic tissues and organs in vitro .